Signs and Cause: A Critical Discourse Analysis of Oppressed Masses: A Case of Jordanian Teachers’ Protest in 2019 - Al Khotaba, Eissa Hamid (Al-Adab Journal, 2023)
Language has a significant contribution to the exchange of knowledge. Scholars examine different uses of language to find out its effect and role in several domains of society such as media, criticisms, politics, and related fields. Discourse analysis is connected with the use of both spoken and written language. It supports in analyzing how users say things, their effect on the audience, and how it influences society, or the way society affects communication. This mixed-mode research aims to provide a systemic analysis on how oppressed masses use signs and symbols through different social media platforms such as Facebook, WhatsApp, Twitter, and Instagram to encourage teachers to protest and achieve parents’ support to prevent their children from going to schools, in a Jordanian context. The sample of the study consisted of 189-selected posters/signs and symbols using a convenient sampling technique. The selected Arabic posters were translated into the English language. The researcher used the analytical instrument adopted from Van Dijk's (2005) framework of political discourse analysis. The corpus was analyzed contextually. The findings of the study showed that in the reaction to meeting demeaning and dismissive discourses, schoolteachers reacted as inheritors of cultural legacies, meaningful resources, context specialists, professionals, and moral authority figures. In addition, the results indicated a strong link between political discourse analysis and the use of sign language that reflects the social practices of protesters and oppressed masses.  To conclude, this study is an add-value to both local and body of knowledge locally, regionally, and internationally concerning theory and practice in which previous experience shows every possible influence to preserve public sustenance, show criticism, and express demands as teachers’ signs and symbols in different provinces in Jordan worked effectively in a civilized manner.